Sustainable Livelihood Security Vis-à-Vis Agricultural Sustainability in India: A Case Study of Karnataka, India - Srinatha, T. N.; Pramod Kumar; Arun, D.; Debasmita Baruah; Praveenkumar A.; Pooja Rajendra Dhange; Anbukkani Perumal (Archives of Current Research International, 2024)
Sustainable Development (SD) has gained prominence as a central focus for development planners, policymakers, and environmental advocates, both nationally and internationally. In India, agriculture grapples with numerous challenges that collectively contribute to sustainability issues, hindering its core goal of ensuring food security. Swaminathan [1] defines Sustainable Livelihood Security (SLS) as encompassing livelihood options that are ecologically sound, economically viable, and socially equitable. The intrinsic connections between SLS and broader welfare objectives such as poverty reduction and human development underscore its pivotal role in achieving sustainable development. This study employs the Sustainable Livelihood Security Index (SLSI) to assess the current status of sustainability in the agriculturally diverse state of Karnataka. Factors like population density, forest cover, cropping intensity, and livestock density are utilized to gauge ecological security. Economic efficiency is measured through per capita income, milk yield, and net sown area, while social equity is assessed by indicators like female literacy, maternal mortality rate, and the percentage of the population below the poverty line (BPL). Despite inherent variations and limitations, these selected variables offer substantial insight into the overall ecological, economic, and equity dimensions of the state. The results reveal a wide range of values for sustainability status (WSLSI), spanning from 0.17 to 0.62, with corresponding ranges of 0.07 to 0.64 for economic efficiency (EEI), 0.17 to 0.77 for ecological security (ESI), and 0.12 to 0.95 for social equity (SEI). This indicates significant disparities in the livelihood security of Karnataka across its ecological, economic, and social dimensions. Notably, the districts of Dakshina Kannada, Udupi, and Chikkamagaluru emerge as top performers in both simple SLSI and weighted SLSI, excelling in all three component indices. Conversely, districts such as Raichur, Yadagiri, and Koppal exhibit lower performance across all indices, highlighting the urgent need for targeted interventions in health, education, and agricultural investment. Strategies such as technological advancements, improved infrastructure, establishment of food processing industries, and enhanced financial and marketing support are recommended to address these disparities and bolster sustainable livelihood security in underperforming districts.